Liikunnanopettajaopiskelijoiden kokema valmius kulttuurisesti moninaisten ryhmien liikunnanopetukseen ja keholliseen kielenopetukseen - Klemettinen, Kaisa; Rancken, Emelie (2024)
The purpose of this master’s thesis was to examine the experiences and attitudes of physical education teacher-students on cultural diversity and embodied language teaching as part of physical education at school. The study aimed to find out how ready the physical education teacher-students feel they are to teach physical education to culturally and linguistically diverse groups. In addition, the aim was to increase understanding of how the physical education teacher-students see the role of the physical education teacher and embodied language teaching in a diversifying school world. The study was carried out as a qualitative study. The research material has been collected from the equality courses of the Faculty of Sport and Health Sciences at the University of Jyväskylä, as part of the ELLA project funded by the Kone Foundation (01/2021–12/2024; Project number 202007315). The research material was collected by the course teacher and consisted of ten physical education students’ interviews (2021) and 33 students’ answers (2023) to six open questions. The data was analyzed using theory-guided content analysis. In the study, a model of intercultural competence served as the theoretical framework. The main findings of the study were that physical education teacher students experienced cultural and linguistic diversity as a growing part of physical education teacher’s work, and that the work of a teacher requires a lot of intercultural competence. The students felt that the integration of pupils from different cultures into the school and Finnish society, was also the responsibility of the physical education teacher. Teacher-students saw physical education classes as an important part of the integration process for students who immigrated to Finland, as well as a good opportunity to learn the Finnish language. From the experiences and attitudes of the students, it emerged that they had a good capability and knowledge for both equal, cultural diversity-promoting physical education and embodied language teaching in connection with physical education. However, students also raised insecurities about their own competence which can affect the utilization of their competence in working life. The results of the study confirm the importance of courses containing themes about cultural diversity and language teaching as part of the physical education teacher training to develop as a physical education teacher in a diversifying society. Furthermore, the results indicate that even short-term learning experiences can generate important insights and interest, as well as promote understanding and confidence in teaching culturally and linguistically diverse groups of pupils.